1965
DOI: 10.1037/h0022011
|View full text |Cite
|
Sign up to set email alerts
|

Recognition memory for random shapes as a function of complexity, association value, and delay.

Abstract: 12 groups of 24 Ss each were examined on 2 tests at 3 delays for recognition accuracy of random shapes having 2 levels of complexity and 2 levels of association value (A). A measure of form coding was also taken. Forms of high A were more accurately recognized than forms of low A, and a 2nd recognition test on the same forms resulted in a practice effect for simple but not for complex forms. All delay effects were insignificant. Complex form coding was positively related to A. Simple form coding was infrequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
2

Year Published

1968
1968
1984
1984

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 9 publications
3
33
2
Order By: Relevance
“…The effect holds for words (Craik & Lockhart, 1972), faces (Bower & Karlin, 1974;Warrington & Ackroyd, 1975), colors (Brown & Lenneberg, 1954), complex forms (Clark, 1965;Daniel & Ellis, 1972), environmental sounds (Bartlett, 1977), pictures (Bower, Karlin, & Dueck, 1975;Freedman & Haber, 1974), and now odors (Rabin & Cain, 1984). The present experiment extends this knowledge by showing that short-term odor recognition may also benefit from semantic encoding.…”
Section: Discussionsupporting
confidence: 66%
“…The effect holds for words (Craik & Lockhart, 1972), faces (Bower & Karlin, 1974;Warrington & Ackroyd, 1975), colors (Brown & Lenneberg, 1954), complex forms (Clark, 1965;Daniel & Ellis, 1972), environmental sounds (Bartlett, 1977), pictures (Bower, Karlin, & Dueck, 1975;Freedman & Haber, 1974), and now odors (Rabin & Cain, 1984). The present experiment extends this knowledge by showing that short-term odor recognition may also benefit from semantic encoding.…”
Section: Discussionsupporting
confidence: 66%
“…Future research might use different kinds of stimuli and at least several levels of complexity in an attempt to determine whether or not the complexity of individual stimulus events does influence remembered duration in a predictable way. Like some previous studies (e.g., Clark, 1965), Experiment 1 found no effect of stimulus complexity on recognition memory. This suggests that data that show an effect of event complexity on remembered duration cannot be explained in terms of Ornstein's storage size hypothesis, which regards memory for individual stimulus events as important.…”
Section: Discussionmentioning
confidence: 44%
“…There was no significant effect of type of pattern on recognition memory [F{1,58) = 3.22, MSe = .036, p > .05]. Others (e.g., Clark, 1965) also have found no effect of stimulus complexity on recognition performance. However, performance was significantly greater than zero, or "chance," for the simple patterns, but not for the complex ones (means of .085 and .023, respectively).…”
Section: Resultsmentioning
confidence: 90%
“…For example, in a study that was published a few years ago (Clark, 1965), groups of Ss observed 10 simple or 10 complex shapes of high or low association value, and later attempted to recognize them in a forced-choice recognition test. Figures I and 2 show the shapes used in that study.…”
mentioning
confidence: 99%